MENJAGA KELESTARIAN LINGKUNGAN MARITIM PESISIR YANG BERKELANJUTAN DI KABUPATEN PIDIE DENGAN PENDEKATAN ADAT LAOT - Rahcmad Munazir; Zulfan Yusuf; Mujiburrahman Mujiburrahman; Muhammad Nur (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This research is a study that focus on local wisdom aspect as the force behind the sustainable development, whether development in economic, social, culture, education and other aspects. The scope of this research problem is coastal development based on the local coastal wisdom itself. Where wisdom is positioned as a potential for environmentally friendly and sustainable development. So this study looks at how the strategy of Panglima Laot as an institution of adat laot or local wisdom which is a maritime cultural heritage that developed in Aceh coast in maintaining sustainable coastal environment. This research was conducted in Pidie District of Aceh Province, where Pidie District is one of the coastal regency in Aceh. By borders, the North side of the regency is bounded by the Malacca Strait, South by West Aceh and Aceh Jaya Regencies, the East with Pidie Jaya Regency and the West is bounded by the Regency of Aceh Besar. This research uses qualitative research methods. In addition, the study also uses a multi-disciplinary approach. The approach used in this research is the approach of sociology, anthropology and history. The existence of three disciplinary approaches, can provide a comprehensive description of Panglima Laot, so that the researchers can build concepts in answering research problems. The results of this study indicates that, Panglima Laot as chief of adat (custom) has its own role in regulating fishermen as coastal custom communities. The existence of Panglima Laot is strategic enough in limiting the behavior of fishing communities, especially behavior that can damage the coastal environment. To curb such behavior, the Panglima Laot undertook by customary approach as a strategy in preventing the destruction to the coastal environment caused by the behavior of fishermen. The customary approach strategy used by panglima laot as adat leader in encouraging sustainable coastal maritime conservation in Pidie District.